Вответе не должно быть переменных. решить : . 2y/y+3 + (y-3)во 2 степени умножить(2/9-6y+y(квадрат) + 1/9-y(квадрат))

саша10041 саша10041    3   07.07.2019 09:10    0

Ответы
zzzzmi zzzzmi  30.07.2020 11:42
1)     2         +     1   =       2     +        1          = 2(3+y)+3-y =
    9-6y+y²        9-y²      (3-y)²      (3-y)(3+y)       (3-y)²(3+y) 
= 6 +2y+3-y =        9+y     
   (3-y)²(3+y)    (3-y)²(3+y)

2)  (y-3)² *       9+y         = (-1(3-y))² * (9+y)  = (-1)² (3-y)² (9+y)  =
                  (3-y)²(3+y)           (3-y)²(3+y)               (3-y)²(3+y)
= 9+y
   3+y

3)  2y  +  9+y  =  2y+9+y = 9+3y = 3(3+y) =  3
    y+3     3+y          y+3       y+3        y+3
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра